Dzielnica Wzajemnego Szacunku Czterech Wyznań i realizowane w niej programy dydaktyczne oraz ich edukacyjny potencjał - Sanecka, Anna (Instytut Pedagogiki Uniwersytetu Wrocławskiego, 2017)
The Quarter of Mutual Respect of Four Denominations has been the place where different educational programmes are held for 18 years. Some of them lay emphasis on presenting different religions and denominations which exist in the Quarter, others concentrate on interreligious and/or interdenominational dialogue. But all of them have some common features. 1) All the programmes give some educational message concerning different religions and denominations – different from the religion or denomination of programme participants or their own religion or denomination which they do not know very well. 2) They underline the presence of religion – or even religions – in the public space. 3) They teach the openness and tolerance towards different outlooks, value systems and ways of life.
Keywords: denomination; dialogue; educational project; meeting; multireligion; religion; The Quarter of Mutual Respect of Four Denominations